2018
DOI: 10.1134/s1607672918010040
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Genes—Potential Therapy Targets—and Their Relationship to Survival in Renal Cell Carcinoma

Abstract: The main mechanisms of pathogenesis of clear cell renal cell carcinoma (CCRCC) are realized through the PI3K-AKT-mTOR and Ras-RAF-ERK signaling pathways. Targeted therapy is directed primarily at the genes and their encoded products that are components of these pathways. The levels of expression and coexpression of target genes were determined, and the difference in the functioning of the genes of one of the two major signaling pathways in tumors of CCRCC patients with different life duration (more and less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…This subtype is notoriously resistant to traditional chemotherapy and radiotherapy (52). The primary signaling pathways underlying ccRCC pathogenesis include the PI3K/AKT and MAPK signaling pathways (53). Elevated Notch1 signaling exerts its tumor growth-promoting effects via the PI3K/AKT signaling pathway (54,55) and the oncogenic effects of specific microRNAs and the long non-coding RNA, promoter of CDKN1A antisense DNA damage activated RNA, also involve the activation of this pathway (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…This subtype is notoriously resistant to traditional chemotherapy and radiotherapy (52). The primary signaling pathways underlying ccRCC pathogenesis include the PI3K/AKT and MAPK signaling pathways (53). Elevated Notch1 signaling exerts its tumor growth-promoting effects via the PI3K/AKT signaling pathway (54,55) and the oncogenic effects of specific microRNAs and the long non-coding RNA, promoter of CDKN1A antisense DNA damage activated RNA, also involve the activation of this pathway (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…The principal mechanisms involved in renal carcinoma pathogenesis seem to be mediated via PI3K-AKT-mTOR, Ras-RAF-ERK, and VEGF signaling pathways, and the level of expression of the genes that are components of these pathways was positively correlated with overall survival in these patients. Therefore, further research targeting the genes and their encoded products, within these pathways, is needed to provide more insight into the involved pathways [ 92 , 93 ].…”
Section: Ckd and Malignancy—dangerous Scenarios In The Framework Omentioning
confidence: 99%
“…The PI3K/AKT/mTOR and MAPK pathway is renowned for its activity in the development of RCC [ 26 ]. Recently, studies have revealed that the release of inflammatory cytokines, such as IL-2, IL-6, IL-10, and TNF- α , and the activity of ROS which initiated RCC are modulated by the MAPK pathway [ 27 ].…”
Section: Discussionmentioning
confidence: 99%